Digital rule-based compliance processes. The urban regeneration of ex-Corradini, Naples (IT) - Marina Rigillo; Sergio Russo Ermolli; Giuliano Galluccio (Agathón)
The paper investigates the cultural and technical transformations in architectural design produced by digital technologies, considering ‘data’ as a strategic asset for the definition of new connections between the physical environment, virtuality and digitalization in order to improve the decision-making processes underpinning design choices. The article explores the case of the urban regeneration of the Corradini ex-industrial area in Naples, offering an experimental application of rule-based compliance protocols within a high informative uncertainty context. The application of BIM-based procedures in the early design process stage becomes an opportunity to develop a multi-scenario approach, which employs Code and Model Checking systems as ‘heuristic’ tools to support decisions and enhancing risk management in complex projects.